Renal cell carcinoma in childhood - Barros,Luciano R. (2004)
The renal cell carcinoma (RCC) rarely occurs in childhood. We report here 3 cases of RCC in children. Two girls and 1 boy aged 14, 8 and 13 years old, respectively, presented with gross hematuria as their main complaint. They underwent ultrasonography and computerized tomography, which revealed unilateral renal tumor with lymph nodal involvement in all 3 cases. They were treated with radical nephrectomy associated with regional lymphadenectomy, with histopathology of RCC. Incomplete adjuvant radiotherapy was performed in 2 cases and no complementary treatment in the other one. All are disease-free in a period ranging from 9 to 77 months after diagnosis. Radical nephrectomy associated with regional lymphadenectomy is the best treatment for RCC in childhood. The disease appears to have a less aggressive behavior in children.